Brain-derived neurotrophic factor propeptide inhibits proliferation and induces apoptosis in C6 glioma cells. Issue 12 (16th August 2017) - Yang, Bangkun; Qin, Jun; Nie, Ying; Li, Yong; Chen, Qianxue
Abstract : There are several forms of brain-derived neurotrophic factor (BDNF), the precursor of BDNF, mature BDNF, and BDNF propeptide. They exert different effects through different transmembrane receptor signaling systems. Precursor of BDNF is enzymatically cleaved, either by intracellular or by extracellular proteases, to generate mature BDNF and its propeptide (BDNF propeptide). The aim of this study was to evaluate the potential molecular mechanisms that underlie the inhibition of glioma cell growth by the BDNF propeptide. To achieve this, we examined the expression of BDNF propeptide in C6 glioma cells. The 3-(4, 5-dimethylthiazol-2-Yl)-2, 5-diphenyltetrazolium bromide assay and the apoptosis assay were used to assess the effects of the BDNF propeptide on the growth and apoptosis of glioma cells. We found that the BDNF propeptide promoted C6 glioma cell apoptosis and decreased in-vitro cell growth. We also found using western blot that cleaved caspase3 and B cell lymphoma 2 (Bcl2)-associated X protein abundances increased, whereas Bcl2 abundance decreased. Our data suggest that the BDNF propeptide may have an inhibitory effect on glioma through activation of the caspase3 pathway.